2018
DOI: 10.1016/j.jvs.2018.03.417
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral atherectomy practice patterns in the United States from the Vascular Quality Initiative

Abstract: Despite a lack of evidence for atherectomy over angioplasty and stenting, its use has increased across the United States from 2010 to 2016. It is applied equally to IC and CLI populations, with no identifiable pattern of comorbidities or lesion characteristics, suggesting that indications are not clearly delineated or agreed on. This study places impetus on further understanding of the optimal role for atherectomy and its long-term clinical benefit in the management of peripheral arterial disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The initial wave of enthusiasm for debulking plaque and attaining similar long-term patency without the need for adjunctive stenting led to a surge in atherectomy procedures. 33,34 More recently, atherectomy has been used in combination with drug-coated balloon angioplasty. 33,[35][36][37] Nonetheless, evidence for the clinical effectiveness of atherectomy is lacking compared with existing balloon angioplasty and stenting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The initial wave of enthusiasm for debulking plaque and attaining similar long-term patency without the need for adjunctive stenting led to a surge in atherectomy procedures. 33,34 More recently, atherectomy has been used in combination with drug-coated balloon angioplasty. 33,[35][36][37] Nonetheless, evidence for the clinical effectiveness of atherectomy is lacking compared with existing balloon angioplasty and stenting.…”
Section: Discussionmentioning
confidence: 99%
“…33,34 More recently, atherectomy has been used in combination with drug-coated balloon angioplasty. 33,[35][36][37] Nonetheless, evidence for the clinical effectiveness of atherectomy is lacking compared with existing balloon angioplasty and stenting. Investigators have suggested that the greater reimbursement for atherectomy procedures might be associated with the increased use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This number is significantly higher than the 15% published in the Vascular Quality Initiative. 10 There have been studies showing a benefit of atherectomy in conjunction with angioplasty 11 being practiced by our group. As discussed in the results, we did not have any complications from atherectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Atherectomy devices are increasingly used in endovascular interventions for the treatment of peripheral arterial disease (PAD), despite inconclusive evidence of their efficacy compared with more conventional therapies such as percutaneous transluminal angioplasty (PTA) and stenting. [1][2][3] Rather than forcing atherosclerotic plaque away from the lumen as in PTA and stenting, atherectomy debulks and removes plaque from occluded arteries by vaporizing (laser), pulverizing (orbital), or cutting (excisional). 4 The theoretical advantages of atherectomy have not consistently translated into improved clinical outcomes and increased enthusiasm is inconsistent with an emerging body of evidence.…”
Section: Introductionmentioning
confidence: 99%